Menjembatani Literasi Fisik: Metode Pembelajaran Multilateral dalam Pendidikan Jasmani untuk Meningkatkan Kemampuan Belajar Motorik - Galih Priyambada; Rudi Hartono; Agus Rusdiana; Andri Tria Raharja; Japhet Ndayisenga (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. This study aimed to investigate the impact of multilateral learning methods on the acceleration of motor educability in elementary school students, with an analytical focus on manipulative coordination and sensorimotor adaptability. Materials and methods. Employing a quantitative approach with a pre-experimental one-group pretest-posttest design, this study involved 50 fifth-grade students selected via purposive sampling. The pedagogical intervention was implemented over a six-week period, integrating multilateral principles into the formal physical education curriculum through small sided games and fundamental movement circuits. Assessment instruments specifically tennis ball throwing and catching tests alongside basketball throwing tests were utilized to evaluate the efficacy of force control and the students' capacity for adaptive calibration to variability in object mass. Data were subsequently analyzed using a paired samples t-test at a 5% significance level to determine the statistical significance of the intervention's impact Results. The results demonstrated a significant increase in motor performance across both measurement parameters; the mean score for the tennis ball throw significantly increased from 7.74 to 8.00 (t_observed = 2.768 > t_table = 2.009; p = 0.008). A more substantial significance was identified in the basketball instrument, where scores rose from 3.07 to 3.37 (t_observed = 9.440 > t_table = 2.009; p < 0.001). These findings provided empirical evidence that multilateral intervention effectively stimulated neuromuscular plasticity in students, enabling precise force calibration during transitions in object characteristics. Conclusions. It was concluded that the implementation of multilateral learning based on equipment modification was a significant strategy for optimizing motor educability profiles while strengthening the foundation of physical literacy in children's developmental phases.